Union of Fact and the Recognition of Inheritance Rights According on Peruvian Civil Law - Amado Ramírez, Elizabeth Del Pilar (2015)
The union actually encompasses a set of multiple and heterogeneous human realities whose common element is being cohabitation (sexual type) that are not marriage. They are characterized precisely by ignoring, delaying or even reject marital commitment. From this we derive serious consequences, example the union in fact had no inheritance rights, until recently, no question, was unanimously noted that the spouse is not inherit. However, at the policy level, the prejudices that obeyed the closed concept of family and marriage, have fallen by the wayside since the Constitution of 1993 which followed the trend of international treaties grants broad protection even when not bound by a marriage. The succession of the legitimate domestic partners law states that 30007 recognizes a social status that is increasing and that the state is obliged to protect union members actually own because it creates emotional ties, subsidiaries and equity , materializing the top-right of equality between marri